Intimate Relationships Buffer Suicidality in National Guard Service Members: A Longitudinal Study. Issue 6 (3rd December 2018) - Blow, Adrian J.; Farero, Adam; Ganoczy, Dara; Walters, Heather; Valenstein, Marcia
Abstract : Objective: Members of the U.S. military are at a high suicide risk. While studies have examined predictors of suicide in the U.S. military, more studies are needed which examine protective factors for suicide. Informed by the interpersonal theory of suicide, this study examined the strength of the intimate relationship and its role as a buffer of suicidality in National Guard service members. Method: A total of 712 National Guard residing in a Midwestern state, who had all recently returned home from a deployment, took part in this study and completed surveys at 6 and 12 months postdeployment. They were assessed on suicide risk, mental health (depression, post‐traumatic stress disorder, anxiety), and relationship satisfaction. Results: Lower relationship satisfaction and more depressive symptoms at the 6‐month assessment were significantly related to greater suicide risk at 12 months. Each interaction between couple satisfaction and three mental health variables (PTSD, depression, and anxiety) at the 6‐month assessment was significantly associated with suicide risk at 12 months. Conclusions: The strength of the intimate relationship serves as a buffer for suicide in National Guard service members who have PTSD, anxiety, or depression. Interventions that strengthen these intimate relationships could reduce suicide in service members.